Mitosis and Meiosis / Part B - Maiato, Helder; Schuh, Melina (Mitosis and Meiosis, 2018)
"Mitosis and Meiosis, Part B, Volume 145, a new volume in the Methods in Cell Biology series, continues the legacy of this premier serial with quality chapters authored by leaders in the field. Unique to this updated volume are chapters on Mitotic live cell imaging at different time scales, the characterization of mitotic spindle by multi-mode correlative microscopy, STED microscopy of mitosis, Correlating light microscopy with serial block face scanning electron microscopy to study mitotic spindle architecture, quantification of three-dimensional spindle architecture, Imaging based assays for mitotic chromosome condensation and dynamics, and more.Contains contributions from experts in the field from across the worldCovers a wide array of topics on both mitosis and meiosisIncludes relevant, analysis based topics"--